Considerations for integrative environmental assessments of contaminated estuarine sediments - Caeiro, Sandra (2021)
Purpose – The purpose of this paper is to discuss integrative environmental assessments applicable to estuarine sediments, including the advantages and limitations of different lines of evidence that could form part of such assessments and their application to ecosystem services. Design/methodology/approach – Weight of evident framework integrating multiple lines of evidence for sediment quality assessment. Findings – Integrative environmental assessments are required to fully address the risks to resident fauna of anthropogenic contaminants deposited in estuarine sediments. Originality/value – The paper presents an updated discussion of the methodologies for environmental assessments of contaminated estuarine sediments.